Penyuluhan Kesehatan Mengenai Bahaya Kecanduan Video Pornografi di SMK Negeri 16 Jakarta Pusat - Ajeng Dwi Retnani; Suryani Hartati (Universitas Muhammadiyah Manado, 2024)
Adolescence is the age of growth for physical, social, and thinking power for the level of knowledge. They go through a period called puberty, which is when individuals reach sexual maturity. This age is filled with high curiosity and the desire to try something new. Freedom and ease in accessing various content both on social media and the internet can have both positive and negative impacts. Ease of access, one of which is pornographic content, can be easily accepted and viewed by the public, especially teenagers. Pornography addiction in teenagers has the impact of destroying their future. The main target is cognitive abilities which will then influence the process of thinking, remembering and recalling recorded data stored in the brain. So, this community service activity aims to provide knowledge to 26 students of SMK Negeri 16 Central Jakarta class XIIA about the dangers of pornographic video addiction in teenagers. This activity method uses lecture and question and answer methods. The author conveys the meaning of pornography, types of pornography, influencing factors, the dangers of pornography addiction and the role of nurses in preventing addiction to pornographic videos in adolescents. Students played an active role in the activity process and there was an increase in posttest scores as much as 78% of students answered well. The author hopes that students can apply it in everyday life so as to avoid addiction to pornographic videos.